Sains Dan Guru Sebagai Agen Transformasi(Analisis Semiotik Terhadap Karya Puisi Ahmad Syauqi) - Ahmad Rais TM (CV. SINAR HOWUHOWU, 2026)
Ahmad Shawqi’s poetry not only presents linguistic beauty but also depicts scientific development and social change through various symbols. This study aims to analyze the denotative, connotative, and mythological meanings in Ahmad Shawqi’s poetry using Roland Barthes’ semiotic approach. The research employs a descriptive qualitative method with documentation techniques. The findings reveal that symbols such as birds, wings, steel, fire, and stars represent the advancement of modern science and technology. Furthermore, the poem highlights the role of education and teachers as agents of social transformation in shaping human civilization. Therefore, Ahmad Shawqi’s poetry is not merely aesthetic in nature but also conveys messages about the importance of science and education in modern life.